The judicial oversight of the democratic process : a republican approach - Marques Neto, Pedro (2023)
Why and based on which types of reasons should courts review the organization of the democratic process by the legislature? This thesis investigates two distinct answers to this question. The first approach defends the constitutionalization of core principles of political equality. Under this model, courts should employ a balancing test in which individual rights to equal political participation are weighted against state interests in their limitation. The second approach upholds instead the constitutionalization of political competition. Under this model, courts should focus on the background structures that enable a competitive politics to emerge and flourish, undertaking an antitrust-style analysis of conflicts over the proper organization of the democratic process. This thesis argues for an intermediate republican approach, according to which courts should try to minimize certain harms to the democratic process associated with political domination. This approach underlines the dual nature of democratic rights: they are rights that protect individual interests and actions (the right to vote being the most fundamental) that can be realized and be made sense of only in the context of a normative framework and institutional infrastructure provided and implemented by the state. The approach also underlines the role of courts, as neutral arbiters to political disputes, in preserving a minimal level of integrity in the democratic structures and procedures that make the practice of collective self-government possible. From the perspective of the republican approach, the thesis then examines some recent decisions of the Brazilian Supreme Court and Superior Electoral Court on the law of democracy. It argues that the type of harm to the democratic process tackled by these courts tend to be highly structural in nature, concerning the quality of political representation and electoral competition in the country. The courts also display a heightened trust in the judicial ability to properly identify and remedy the structural harms under analysis vis-à-vis the political process. The outcome is often a more intrusive judicial review of electoral mechanisms on the courts part. Based on the republican account of the role of courts in the oversight of the law of democracy, the thesis reinterprets such decisions, offering a map and a vocabulary for understanding the past and envisioning the future of the judicial oversight of the democratic process in Brazil.